Analysis of Nurse Staffing Needs Methods in Inpatient Room at Hospital : Literature Review - Muhammad Shiddiq Dwisurya; Sri Sundari; Elsye Maria Rosa (International Journal of Social Service and Research, 2022)
Planning for nurse staffing needs was very important at hospital. Nowadays there are some new methods and tools perform to count nurse staffing needs. The use of correct tools and methods makes hospital run well in quality of service, administration, and also financial. This study aims to analyze various methods that can be used in determining nurse staffing needs in hospital inpatient room. This study using PRISMA / Preferred Reporting Systematic Reviews and Meta-analysis with final result there are 12 literatures for this study. Results of study show that there is no definite requirement which method should be used from a country in the literature to calculate nursing staff compliance. There are only recommendations from the government or associations rather than professional organizations from each country which method that have good recommendation. Thus, each method has its own way of providing insight into the number of nurses needed in the inpatient room. Each method is interrelated and the calculation results often differ from one method to another.